Effects of a potentiated zinc oxide on growth performance, incidence of diarrhea, mineral excretion, and bone breaking strength of nursery pigs (Research, Society and Development, 2022)
The objective of the present study was to evaluate the effects of a potentiated (PZnO) and conventional source of zinc oxide (ZnO) on growth performance, bone breaking strength, incidence of diarrhea, and fecal excretion of phosphorus (P), zinc (Zn), and copper (Cu) of nursery pigs. A total of 84 pigs weaned at 21 d of age (6.1 ± 0.9 kg) were allotted based on a completely randomized block design. The nutritional program was divided in four dietary phases with four dietary treatments: [NC negative control: no ZnO and regular P levels (0.440; 0.420; 0.400; 0.380%); PC positive control: inclusion of ZnO (3,000, 3,000, 2,200, 1,000 ppm) and regular P levels (0.440; 0.420; 0.400; 0.380%); ZnO + PZnO: association between ZnO (1,000, 1,000, 500, 0 ppm) and PZnO (500, 500, 500, 500 ppm) and 10% low P levels (0.396; 0.379; 0.360; 0.340%); PZnO: inclusion of the PZnO (500, 500, 250, 250 ppm) and 10% low P levels (0.396; 0.379; 0.360; 0.340%)]. Data were analyzed using the GLM procedure of SAS 9.4. Pigs fed diets supplemented with PZnO increased overall ADFI (P < 0.05) when compared with treatment with ZnO. Pigs fed diets supplemented with PZnO reduced (P < 0.05) Zn excretion when compared to treatment with ZnO. The treatments with PZnO reduced (P < 0.05) P excretion during phase 3 when compared with treatment with ZnO. In conclusion, the use of PZnO supplemented at lower levels than the conventional source of ZnO, can be a potential alternative to reduce the environmental impact of the swine production systems by optimizing the P utilization, reducing Zn excretion, and still maintaining an optimal feed intake.